2004
DOI: 10.1128/jvi.78.19.10738-10746.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Human Papillomavirus Type 8 E2 Protein Suppresses β4-Integrin Expression in Primary Human Keratinocytes

Abstract: Human papillomaviruses (HPVs) infect keratinocytes of skin and mucosa. Homeostasis of these constantly renewing, stratified epithelia is maintained by balanced keratinocyte proliferation and terminal differentiation. Instructions from the extracellular matrix engaging integrins strongly regulate these keratinocyte functions. The papillomavirus life cycle parallels the differentiation program of stratified epithelia, and viral progeny is produced only in terminally differentiating keratinocytes. Whereas papillo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 49 publications
4
43
0
2
Order By: Relevance
“…The selective advantage of the frequent loss of E2 in cervical cancers induced by HPV16 or 18 has been explained by E2-mediated suppression of the viral E6/7 promotor, which is not relevant in transgenic mice, and by the induction of senescence or apoptosis (38)(39)(40). Interestingly, HPV8 E2 expressing keratinocytes do not undergo apoptosis (41), which may suggest that it has at least no inhibitory effect on carcinogenesis. Further studies are under way to test whether the increased levels of E2 may promote transformation.…”
Section: Resultsmentioning
confidence: 99%
“…The selective advantage of the frequent loss of E2 in cervical cancers induced by HPV16 or 18 has been explained by E2-mediated suppression of the viral E6/7 promotor, which is not relevant in transgenic mice, and by the induction of senescence or apoptosis (38)(39)(40). Interestingly, HPV8 E2 expressing keratinocytes do not undergo apoptosis (41), which may suggest that it has at least no inhibitory effect on carcinogenesis. Further studies are under way to test whether the increased levels of E2 may promote transformation.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the papillomavirus E2 proteins are transcription factors that effectively antagonize the ability of E6 and E7 to block senescence (19), although the precise mechanisms are unknown. Recent studies showed that when expressed alone in cell lines or primary keratinocytes, certain E2 proteins directly downregulate ␤4-integrin (and to some extent ␤1-integrin) expression (36). In vivo, decreased ␤4-integrin expression is associated with terminal differentiation of stratified epithelia and is manifest by a loss of epithelial cell adhesion, altered cell morphology, and egress from basal to suprabasal layers (11,17), suggesting that E2 causes senescence by a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The recent discovery that human papillomavirus type 8 E2 protein produces similar changes in cellular morphology when expressed in epithelial cells may provide new insights into KSHV TK functions as well (36). Notably, the papillomavirus E2 proteins are transcription factors that effectively antagonize the ability of E6 and E7 to block senescence (19), although the precise mechanisms are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…binding in the promoter region and displacement of cellular factors (36). In MMP-9, however, binding of E2 to the promoter region is not required for induction, which is mediated predominantly through the presence of an AP-1 site in close proximity to the transcription start site (31,34).…”
Section: Discussionmentioning
confidence: 99%